2006 International Workshop on Satellite and Space Communications 2006
DOI: 10.1109/iwssc.2006.255999
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Mobility Aspects for DVB-S2/RCS Broadband Systems

Abstract: In this paper we address the emerging application of mobility to DVB-RCS systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…From a standardization point of view, the respective system specifications commonly rely on the digital video broadcasting via satellite second-generation/return channel via satellite (DVB-S2/RCS2) pair of standards [1,2], in the fixed case, and on the digital video broadcasting satellite to handheld (DVB-SH) standard [3], in the mobile case. However, in recent years, the boundary between these two typical system categories is becoming vague because there are efforts for introducing mobility into DVB-S2-based systems in the frame of vehicular, maritime, aeronautical and railway scenarios [4][5][6]. The latter references also include a long listing of relevant ESA ARTES (European Space Agency Advanced Research in Telecommunications Systems), European Space Agency Advanced Research in Telecommunications Systems (ESA ARTES), European Union Information Society Technologies (EU IST), Electronics and Telecommunications Research Institute (ETRI ) and industrial programs as well as pre-commercial trial/fully commercial activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…From a standardization point of view, the respective system specifications commonly rely on the digital video broadcasting via satellite second-generation/return channel via satellite (DVB-S2/RCS2) pair of standards [1,2], in the fixed case, and on the digital video broadcasting satellite to handheld (DVB-SH) standard [3], in the mobile case. However, in recent years, the boundary between these two typical system categories is becoming vague because there are efforts for introducing mobility into DVB-S2-based systems in the frame of vehicular, maritime, aeronautical and railway scenarios [4][5][6]. The latter references also include a long listing of relevant ESA ARTES (European Space Agency Advanced Research in Telecommunications Systems), European Space Agency Advanced Research in Telecommunications Systems (ESA ARTES), European Union Information Society Technologies (EU IST), Electronics and Telecommunications Research Institute (ETRI ) and industrial programs as well as pre-commercial trial/fully commercial activities.…”
Section: Introductionmentioning
confidence: 99%
“… The group indicated that the limit below which spectrum spreading is necessary is 30 cm in Ku and 50 cm in Ka band .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, both EU and ESA have sponsored R&D programmes to introduce mobility capabilities to DVB-RCS in order to provide broadband satellite services to collective mobile communities such as passengers of airlines, maritime vessels and high-speed trains [17][18][19]. In particular, high-speed trains are expected to be one of the major communities that will exploit broadband satellite services, even if they have posed special challenges due to the peculiar characteristics of the railroad satellite channel [20].…”
Section: Mobile Dvb-rcs Network and Terrestrial Gap-fillersmentioning
confidence: 99%